KAMPANYE DAN TELEVISI (Analisis Pemberitaan Kampanye Pemilu Legislatif 2009 di TV Borobudur) - Julianto, Edi Nurwahyu (Jurnal The Messenger, 2010)
In the context of the current information age, media power is great considered in the flow of information spread quickly and widely. The political elite use media to socialize the political agenda. Institutions of mass media like television and newspapers is believed to have ability in organizing the production, reproduction and distribution of knowledge significantly. A series of symbols that gives meaning of the reality of "there" and experience in life, can be transformed in the public sphere of mass media, which can be accessed by members of society. Public trust what was presented in the media. Media does have a significant force in the conduct of production and reproduction of political image and content of media as a reality that has been constructed (constructed reality).